Anti-CD20 monoclonal antibodies in Systemic Lupus Erythematosus. (January 2021) - Shah, Kavina; Cragg, Mark; Leandro, Maria; Reddy, Venkat
Abstract: Systemic Lupus Erythematosus (SLE) is an autoimmune inflammatory condition with a wide spectrum of disease manifestations and severities, resulting in significant morbidity and mortality. The aetiopathogenesis of SLE is complex. Young women and certain ethnicities are commonly affected, suggesting a significant hormonal and genetic influence. Diverse immunological abnormalities have been described. A characteristic abnormality is the presence of autoantibodies, implicating a central role for B cells in disease pathogenesis and/or perpetuation. Whilst conventional therapies have improved outcomes, a great unmet need remains. Recently, biological therapies are being explored. B-cell depletion therapy with rituximab has been in use off-label for nearly two decades. Inconsistent results between uncontrolled and controlled studies have raised doubts about its efficacy. In this review, we will focus on B cell abnormalities and the rationale behind B-cell depletion therapy with anti-CD20 monoclonal antibody (mAb), rituximab, will be explored including an evaluation of clinical and trial experience. Finally, we will discuss the mechanistic basis for considering alternative anti-CD20 mAbs.